Hadis Bau Mulut Orang Berpuasa Ditinjau dari Pendekatan Bahasa: Analisis Matan secara Hakiki dan Majazi (The Smell of the Mouth of a Fasting Person from a Linguistic Approach: A Literal and Figurative Analysis of the Text) - Sarah Mitha Amelia; Vera Seftia; Muhammad Sofyan Harahap; Laila Sari Masyhur (Journal of Innovative and Creativity, 2025)
The hadith regarding the breath of a fasting person, which states that "The breath of a fasting person is more fragrant to Allah than the scent of musk" (HR. Bukhari and Muslim), is a significant text rich in linguistic and spiritual meaning. This study analyzes the matan (text) of the hadith through a linguistic approach, focusing on its hakiki (literal) and majazi (figurative) interpretations. Literally, the hadith refers to the physical phenomenon of the breath’s odor during fasting, but figuratively, the breath symbolizes sacrifice, sincerity, and devotion, which hold immense value in the sight of Allah, with musk representing spiritual excellence. The analysis examines linguistic devices such as metaphor and hyperbole, the cultural context of Arab society, and interpretations by scholars like Ibn Hajar al-Asqalani and al-Nawawi. The findings demonstrate that this linguistic approach not only enriches the understanding of the hadith’s meaning but also underscores its relevance in fostering sincerity and patience in worship. This study contributes to the development of language-based methodologies for hadith studies and strengthens the connection between linguistics and hadith scholarship within the Islamic intellectual tradition.